Coastal climate change, vulnerability and age friendly communities: Linking planning for climate change to the age friendly communities agenda. (April 2016) - Krawchenko, Tamara; Keefe, Janice; Manuel, Patricia; Rapaport, Eric
Abstract: In light of the global, unprecedented and enduring phenomenon of population ageing, cities and communities across the world have committed themselves to establishing and implementing age friendly community designs, programs, services and practices. In Canada, there has been a particular interest in promoting 'age friendliness' in rural and remote communities where there is often a concentration of older residents and limited access to services and supports. Our study examines the connection between social and place vulnerability and the development of 'age friendly' communities in one Canadian province, Nova Scotia—a province that is at the forefront of the aging trend. Specifically, we look at how infrastructure and assets important to vulnerable seniors in rural communities may be affected by coastal climate change and consider how communities can better plan for such eventualities. This work highlights the importance of linking age friendly community initiatives to proactive planning practices. Substantively, we demonstrate the lack of attention to place vulnerability within the age-friendly communities framework. Highlights: We map the affects of coastal climate change on assets important to seniors in rural, aging communities in Nova Scotia, Canada and review the municipal policy environment. The municipalities in our study areas do not presently have mechanisms in place to consider how future land use planning and controls can secure the safety of their aging citizenry in lieu of changing environmental conditions along the coast. Our study offers a way for rural coastal communities to map these changes and adopt proactive planning practices for climate change mitigation and adaptation within the broader framework of an age friendly community agenda.